Embryonic, Larval, and Early Juvenile Development of the Tropical Sea Urchin, Salmacis sphaeroides (Echinodermata: Echinoidea) - M. Aminur Rahman; Fatimah Md. Yusoff; A. Arshad; Mariana Nor Shamsudin; S. M. N. Amin (The Scientific World Journal)
Salmacis sphaeroides (Linnaeus, 1758) is one of the regular echinoids, occuring in the warm Indo-West Pacific, including Johor Straits, between Malaysia and Singapore. In order to investigate the developmental basis of morphological changes in embryos and larvae, we documented the ontogeny of S. sphaeroides in laboratory condition. Gametes were obtained from adult individuals by 0.5 M KCl injection into the coelomic cavity. Fertilization rate at limited sperm concentration (10−5 dilution) was 96.6±1.4% and the resulting embryos were reared at 24°C. First cleavage (2-cell), 4-cell, 8-cell, 16-cell, 32-cell, and multicell (Morulla) stages were achieved 01.12, 02.03, 02.28, 02.51, 03.12, and 03.32 h postfertilization. Ciliated blastulae with a mean length of 174.72±4.43 μm hatched 08.45 h after sperm entry. The gastrulae formed 16.15 h postfertilization and the archenteron elongated constantly while ectodermal red-pigmented cells migrated synchronously to the apical plate. Pluteus larva started to feed unicellular algae in 2 d, grew continuously, and finally attained metamorphic competence in 35 d after fertilization. Metamorphosis took approximately 1 h 30 min from attachment to the complete resorption of larval tissues and the development of complete juvenile structure with adult spines, extended tubefeet and well-developed pedicellaria, the whole event of which usually took place within 1 d postsettlement. This study represents the first successful investigation on embryonic, larval, and early juvenile development of S. sphaeroides. The findings would greatly be helpful towards the understanding of ontogeny and life-history strategies, which will facilitate us to develop the breeding, seed production, and culture techniques of sea urchins in captive condition.